Categories of experience amongst the Xhosa : a psychological study - Schweitzer, Robert David (Rhodes University, Faculty of Humanities, Department of Psychology, 1977)
Transcultural studies of psychological states may be seen as falling within two schools, one adopting a position in which universal criteria of "mental health" are assumed, the other a cultural relativist position in which phenomena are understood in terms of the context in which they occur. The present study, in adopting the latter position, examines categories of experience amongst the Xhosa in terms of their meaning within Xhosa cosmology. The thoughts and practices of a Xhosa Iqgira (diviner) were extensively examined using an idiographic approach. This was corroborated by in-depth interviews with his consultees who were undergoing the categories being studied. Three categories, thwasa, phambana and amafufunyana are explicated. Thwasa is seen to be related to the individual- shade communion. Phambana is predominantly related to custom and witchcraft. Amafufunyana is related to disharmonious interpersonal situations within the community. The universalist position, derived from descriptive psychiatry, has often viewed the mental status of amaqgira {diviners) as neurotic or even psychotic. This finding is not supported in the present study. The implications of the research for community mental health in Southern Africa are discussed.
Keywords: Xhosa (African people) -- Psychology